2018
DOI: 10.1152/ajpendo.00134.2018
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 suppresses cholesterol accumulation in the liver of growth hormone-deficient mice via the activation of ABCA1

Abstract: Recently, several clinical studies have suggested that adult growth hormone deficiency that also has low concentration of IGF1 is associated with an increased prevalence of fatty liver (FL). ABCA1 is a pivotal regulator of lipid efflux from cells to apolipoproteins and play an important role on formation of FL. In this study, we determined the effects of IGF1 on ABCA1 expression in GH deficient mice to clarify its effects on FL. Western blotting, real-time PCR and a luciferase assay were employed to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
(62 reference statements)
3
17
0
Order By: Relevance
“…Thus, ABCA1 has a beneficial effect to protect the liver from cholesterol accumulation. This is also confirmed by our recent study that the upregulation of hepatic ABCA1 expression by insulin-like growth factor-1 (IGF-1) or glucagon-like peptide-1 (GLP-1) reduced hepatic cholesterol accumulation in mice [19,20]. In this study, hepatic ABCA1 expression was elevated by 2-ME 2 , which contributed to the reduction of the lipid content in hepatocytes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, ABCA1 has a beneficial effect to protect the liver from cholesterol accumulation. This is also confirmed by our recent study that the upregulation of hepatic ABCA1 expression by insulin-like growth factor-1 (IGF-1) or glucagon-like peptide-1 (GLP-1) reduced hepatic cholesterol accumulation in mice [19,20]. In this study, hepatic ABCA1 expression was elevated by 2-ME 2 , which contributed to the reduction of the lipid content in hepatocytes.…”
Section: Discussionsupporting
confidence: 87%
“…As a cholesterol exporter, ABCA1 exports intracellular cholesterol to HDL in the presence of ApoA-I. Our previous study showed that the upregulation of hepatic ABCA1 induced by insulin-like growth factor-1 (IGF-1) or glucagon-like peptide-1 (GLP-1) decreased the lipid content in HepG2 cells [19,20]. In this study, we demonstrated that 2-ME 2 significantly reduced the cholesterol content to 78 ± 6% of that in the control group.…”
Section: -Me 2 Reduces Lipid Content Via the Pi3k Pathway In Hepg2 Cellsmentioning
confidence: 99%
“…Another study reports that the cAMP-specific inhibitor PDE4 can increase cholesterol efflux by activating ABCA1 expression in human THP-1 and mouse J774.A1 macrophages [ 48 ]. Constitutively active AKT can enhance the promoter activity of ABCA1, and the specific inhibitor PI3K LY294002 has been reported to down-regulate the expression of ABCA1 in mice [ 49 ]. In MC3T3-E1 cells, Liraglutide, an agonist of GLP-1R, has been shown to promote cell proliferation and inhibit cell apoptosis by activating the expression of PI3K/AKT and cAMP/PKA signaling pathways [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Purified pABCA1-LUC was transfected into INS-1 by reagent Lipofectamine2000 (Life Technologies, Gaithersburg, MD, USA). After transfection, cells were maintained in a medium containing HDL or OxLDL for 24 h with or without pre-treatment with LY294002 (10 μM), PD98095 (10 μM), SP600125 (10 μM), or SB203580 (1 μM) to separately inhibit the phosphatidylinositol 3 kinase (PI3K), mitogen-activated protein kinase (MEK), c-Jun N-terminal kinase (JNK), or p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway for 30 min [ 24 ]. Then these cells were lysed by buffer, and the ABCA1 promoter activity was measured according to the manufacturer’s instructions (ToyoInk; Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%